Nociceptor mechanisms underlying pain and bone remodeling via orthodontic forces: toward no pain, big gain - Sheng Wang; Ching-Chang Ko; Man-Kyo Chung; Man-Kyo Chung (Frontiers in Pain Research, 2024)
Orthodontic forces are strongly associated with pain, the primary complaint among patients wearing orthodontic braces. Compared to other side effects of orthodontic treatment, orthodontic pain is often overlooked, with limited clinical management. Orthodontic forces lead to inflammatory responses in the periodontium, which triggers bone remodeling and eventually induces tooth movement. Mechanical forces and subsequent inflammation in the periodontium activate and sensitize periodontal nociceptors and produce orthodontic pain. Nociceptive afferents expressing transient receptor potential vanilloid subtype 1 (TRPV1) play central roles in transducing nociceptive signals, leading to transcriptional changes in the trigeminal ganglia. Nociceptive molecules, such as TRPV1, transient receptor potential ankyrin subtype 1, acid-sensing ion channel 3, and the P2X3 receptor, are believed to mediate orthodontic pain. Neuropeptides such as calcitonin gene-related peptides and substance P can also regulate orthodontic pain. While periodontal nociceptors transmit nociceptive signals to the brain, they are also known to modulate alveolar bone remodeling in periodontitis. Therefore, periodontal nociceptors and nociceptive molecules may contribute to the modulation of orthodontic tooth movement, which currently remains undetermined. Future studies are needed to better understand the fundamental mechanisms underlying neuroskeletal interactions in orthodontics to improve orthodontic treatment by developing novel methods to reduce pain and accelerate orthodontic tooth movement—thereby achieving “big gains with no pain” in clinical orthodontics.